Tinjauan fikih dan astronomis penyatuan matlaâ: menelusuri pemikiran M.S. Odeh tentang ragam penyatuan matlaâ - Nashiruddin, Muh (Sekolah Tinggi Agama Islam Negeri Salatiga, 2012)
The basis of calendar unification or matla constitutes one of the most significant issues relating to the unification effort of Hijra calendar. The popular basis of unification, so far, is based on the union of regional and global matlaâ. The division of matlaâ to regional and global matlaâ is now no longer accurate because it can not accommodate the Hijra calendar pooling ideas in the Islamic world. This paper discusses one of the leading International astronomy thought, Mohammad Shawkat Odeh on varieties of matlaâ unification. He divided the principle of matla unification in to five forms: unification of global matlaâ (one matlaâ for the whole world); the unity of matlaâ in the regions corresponding visibility of hilal; the unity of matlaâ in a similar area of visibility of hilal; the unity of zonal/partial matlaâ; and the unity of local matlaâ. Odehâs thought on the various divisions of matla constitutes new thinking on the concept matlaâ astronomical calculations. He also has presented more detailed thoughts on the division of matlaâ rather than the others.